Criminal Propensity, Social Context, and Recidivism: A Multilevel Analysis of Interactive Relationships. (March 2014) - Wang, Xia; Hay, Carter; Todak, Natalie Erin; Bales, William
With almost 700, 000 inmates released annually in the United States, the predictors of successful reentry have received considerable attention. Prior research documents that recidivism is influenced by both ex-inmate characteristics and social context. Little attention, however, has been paid to the role social context might play in moderating the effects of individual-level risk factors. Using inmate release data from the Florida Department of Corrections and other sources, we examine whether contextual factors that promote crime and antisocial behavior amplify the association between individual criminal propensity and recidivism. Our analysis offers limited support for the moderating effects of context, suggesting that the relationship between criminal propensity and recidivism is substantial and largely independent of community characteristics. We discuss the implications of the findings for theory, research, and policy.